Hubungan Kadar Kreatinin Dengan Hemoglobin Pada Pasien Gagal Ginjal Kronik Sebagai Rujukan Terapi Erythropoietin (EPO) - Tandi Manu, Thomas; Zaena Safitri, Trysia; Urip, Urip; Pauzi, Iswari; Khusuma, Ari (Indonesian Journal Publisher, 2025)
Background: Chronic kidney disease (CKD) is a common condition and a global health problem with various causes that lead to a gradual decline in kidney function, resulting in increased creatinine levels. This condition reduces the production of the hormone erythropoietin (EPO), which stimulates the bone marrow to produce red blood cells, leading to decreased hemoglobin levels and resulting in anemia. Erythropoietin (EPO) therapy represents a primary therapeutic option for the management of anemia in patients with chronic kidney disease (CKD) PurposeTo determine the relationship between creatinine and hemoglobin levels in chronic kidney disease patients as a reference for erythropoietin (EPO) therapy. Methods: This study employed an analytical observational method with a cross-sectional approach by reviewing medical record data. The sample consisted of 56 patients obtained through total sampling. The data were analyzed using the Pearson correlation test. Results: The average creatinine level was 9.92 mg/dL, and the average hemoglobin (Hb) level was 7.96 g/dL. Pearson correlation analysis between creatinine and hemoglobin levels in patients receiving erythropoietin (EPO) therapy showed a statistically significant result with a p-value of 0.001 (<0.05) and a moderate negative correlation (r = -0.436). Conclusion: A significant negative correlation was found between creatinine and hemoglobin levels in patients undergoing EPO therapy, indicating that higher creatinine levels tend to be associated with lower hemoglobin concentrations.